PENGARUH ESTRADIOL-17? DAN KOLAGEN TIPE IV TERHADAP EKSPRESI GEN PIK3CA UNTUK MENGINDUKSI EKSPRESI C-ERBB2 PADA LINI SEL KANKER OVARIUM SKOV-3 - Martgrita, Merry Meryam; Tan, Marselina Irasonia (Perhimpunan Biologi Indonesia, 2016)
Ovarian cancer cell metastasis is induced by signaling pathway activated by the binding of type IV collagen to ?1 integrinreceptor on the surface of cancer cells and estrogen binding to estrogen receptor. However, the role of estradiol-17? andtype IV collagen on the development of ovarian cancer have not been clearly understood. Therefore, this research wasconducted to observe the differential gene expression in SKOV-3 ovarian cancer cells cultured on type IV collagen andtreated with estradiol-17?, and incubated for 12, 24 and 72 hours. Differential display RT-PCR was used to express thedifferential expression gene after treatment. cDNA fragment that expressed differentially was isolated and sequenced.Sequencing result on one of the cDNA fragment showed that PI3K is one of the gene expressed in SKOV-3 ovarian cancercell. To verify this result, cDNA was amplified using PIK3CA specific primer. The increasing level of PIK3CA is inducedby three kinds of receptor activities, those are c-erbB2 receptor bound to estradiol-17?, homodimer receptor of c-erbB2, andthe activity of integrin receptor bound to type IV collagen. The increasing level and activity of PIK3CA can also increasethe expression of c-erbB2 gene. In SKOV-3 cells cultured on type IV collagen for 72 hours, the increasing of PIK3CA andc-erbB2 expression level is very low. The conclusion is that estradiol-17? gives a more significant effect than type IVcollagen to induce the increasing expression of PIK3CA and c-erbB2 genes.Keywords: ovarian cancer, SKOV-3, type IV collagen, estradiol-17?, PIK3CA, c-erbB2